Primary Sclerosing Cholangitis in Very Early Age: Two Case Reports - Nahid, Khan Lamia; Begum, Fahmida; Alam, Rubaiyat; Islam, Mohammed Shahidul; Rukunuzzaman, Md (Bangladesh Journal of Child Health, 2023)
Primary Sclerosing Cholangitis (PSC) is a rare, chronic, progressive cholestatic liver disease which affects intrahepatic and extrahepatic bile ducts. That eventually progresses to end stage liver disease that requires liver transplantation. It mostly occurs in adolescent males and boys. Pediatric disease appears milder in contrast to adult-onset PSC. The diagnosis is made by Magnatic Resonance Cholangiopancreatography (MRCP). Though there is no practical guideline available in pediatric patients for treating PSC UDCA is prescribed chronically in over 80% of patients. There is close association of PSC with inflammatory bowel disease and autoimmune hepatitis in children. So the treatment is complex in case of children. We reported here two cases of PSC, because of rarity of this disease in such a young age. BANGLADESH J CHILD HEALTH 2022; VOL 46 (1) : 30-34